Genomic analysis of contaminant Stenotrophomonas maltophilia, from placental swab culture, carrying antibiotic resistance: a potential hospital laboratory contaminant - Pisut Pongchaikul; Piroon Jenjaroenpun; Paninee Mongkolsuk; Pornpun Vivithanaporn; Thidathip Wongsurawat; Perapon Nitayanon; Iyarit Thaipisuttikul; Jakkrit Khamphakul; Puntabut Warintaksa; Warawut Laolerd; Pitak Santanirand; Piya Chaemsaithong (Scientific Reports)
Abstract Acute chorioamnionitis has been considered as reflective of amniotic fluid infection. Standard microbiological work ups for causative microorganism of intra-amniotic infection is based on microbial identification. However, frequency of positive placental culture is varied depending on placental sampling techniques, contaminations, methods of microbiologic work ups or comprehensive microbiologic work ups. In this report, we performed a hybrid whole genome sequencing of a proven bacterial contaminant obtained from placental culture in a patient with preterm labor and acute chorioamnionitis. This is to unveil genetic characterization of contaminant Stenotrophomonas maltophilia habouring antibiotic resistance genes. Stenotrophomonas maltiphilia was proven to be bacterial contaminant since Ureaplasma urealyticum was subsequently demonstrated in amniotic fluid by 16 S rRNA gene Sanger sequencing. Cultivation results from other sources were no growth. We identified Stenotrophomonas maltiphilia strain RAOG732 which carried several antibiotic resistance genes, including aminoglycoside, fluoroquiolone and beta-lactam. Biofilm production genes were also identified in this genome. We firstly utilized a hybrid sequencing approach to investigate the genome of S. maltiphilia in the patient with preterm and acute chorioamnionitis, a proven bacterial laboratory contaminant. The analysis provided several antibiotic resistance-associated and genes biofilm-associated genes. The detection of S. maltiphilia raised the awareness of the colonization of biofilm-producing bacteria in hospitals, where surveillance for decontamination is necessary.